Fibroblast Growth Factor‐2 Maintains a Niche‐Dependent Population of Self‐Renewing Highly Potent Non‐adherent Mesenchymal Progenitors Through FGFR2c123. (18th June 2012) - Di Maggio, Nunzia; Mehrkens, Arne; Papadimitropoulos, Adam; Schaeren, Stefan; Heberer, Michael; Banfi, Andrea; Martin, Ivan
Abstract: Bone marrow (BM) mesenchymal stem/stromal cells (MSC) are a heterogeneous population of multipotent progenitors currently under investigation for a variety of applications in regenerative medicine. While self‐renewal of stem cells in different tissues has been demonstrated to be regulated by specialized microenvironments called niches, it is still unclear whether a self‐renewing niche also exists for MSC. Here, we show that primary human BM cultures contain a population of intrinsically non‐adherent mesenchymal progenitors (NAMP) with features of more primitive progenitors than the initially adhering colony‐forming units‐fibroblast (CFU‐f). In fact, NAMP could generate an adherent progeny: (a) enriched with early mesenchymal populations (CD146+, SSEA‐1+, and SSEA‐4+); (b) with significantly greater proliferation and multilineage differentiation potential in vitro; and (c) capable of threefold greater bone formation in vivo than the corresponding CFU‐f. Upon serial replating, NAMP were able to regenerate and expand in suspension as non‐adherent clonogenic progenitors, while also giving rise to an adherent progeny. This took place at the cost of a gradual loss of proliferative potential, shown by a reduction in colony size, which could be completely prevented when NAMP were expanded on the initially adhering BM fraction. Mechanistically, we found that NAMP crucially depend on fibroblast growth factor (FGF)‐2 signaling through FGFR2c for their survival and expansion. Furthermore, NAMP maintenance depends at least in part on humoral signals distinct from FGF‐2. In conclusion, our data show a niche/progenitor organization in vitro, in which the BM adherent fraction provides a self‐renewing microenvironment for primitive NAMP. Stem Cells 2012;30:1455–1464